Pendidikan Karakter Melalui Pembelajaran Ips Terhadap Modernisasi Sosial Di Masyarakat - Sulistiawati, Sulistiawati; Rustini, Tin; Wahyuningsih, Yona (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
Education has a very broad purpose and includes various interrelated aspects, of course things that are very important as a source of information, knowledge and general insight. Character education is a place to develop oneself to support the development of an increasingly advanced era. The purpose of this research is that through social studies learning will find out the level of social modernization that exists in society, of course by using character learning to students as a form of preparation for following developments that continue to advance. Technology and information today have a huge impact on the challenges of people's lives. The existence of technology and information proves that the times are increasingly modern. In this study using descriptive qualitative, where in the use of descriptive methods as a description or analysis of a study to determine the effect of character education on social studies learning on the existence of social modernization in society. The results of this study are about character education, character education in social studies learning, social modernization and the role of technology and information. By equipping social sciences through character education related to the social modernization of the younger generation, the impact and influence on life in society can be limited by character education through social sciences.